Woodfuel for urban centres in the Democratic Republic of Congo: The number one energy and forest product returns to the policy agenda - Schure, J.; Ingram, V.J.; Marien, J.; Nasi, Robert; Dubiez, E. (Center for International Forestry Research, 2011)
Policymakers should recognise the size and value of the woodfuel sector and its importance to many people. Harvesters and producers need better access to trees and land to promote better management and reduce conflicts. The tax system for woodfuel should be revised to be transparent and pragmatic. Woodfuel from plantation forests and agroforestry should be favoured over woodfuel from valuable or threatened tree species. More attention should be paid to energy-efficient charcoal kilns and cooking stoves, as well as activities to promote their use. Management options that combine agroforestry, plantations and improving energy efficiency need collaboration from different sectors: energy, forest, land-use planning and agriculture.